Quality of the service and its relation with the self-concept, the social identity and the values - Blesa Matienzo, María Dolores (2008)
A descriptive research correlation design. Sample of 30 universitary students. Different test were used for measure the variables. The age factor does not have a significant linear correlations with self-esteem, being a group young and middle-age volunteers showing  encouragement, self-confidence, and who are able to deal better adaptability which means more effort and perseverance in doing their tasks, with a positive attitude. Regarding multiple regressions study, we may infer the correlation between the variable “social identity” and “quality of attention” and” self- esteem” and “values”.